2015
DOI: 10.18632/oncotarget.6766
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous gene silencing of KRAS and anti-apoptotic genes as a multitarget therapy

Abstract: Pancreatic cancer is one of the most lethal tumor types worldwide and an effective therapy is still elusive. Targeted therapy focused against a specific alteration is by definition unable to attack broad pathway signaling modification. Tumor heterogeneity will render targeted therapies ineffective based on the regrowth of cancer cell sub-clones. Therefore multimodal therapy strategies, targeting signaling pathways simultaneously should improve treatment.SiRNAs against KRAS and the apoptosis associated genes BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…These results demonstrate that PANC-1 and MIA PaCa-2 cell growth is sustained on KRAS expression, and KRAS inhibition, but not TFEB inhibition, increased apoptosis. This is in good agreement with our published results of simultaneous gene silencing of KRAS and apoptotic genes (18). Both primary PDAC cell lines (PANC-1, MIA PaCa-2) express activating mutations of KRAS and inactivating mutations of the P53 gene (31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results demonstrate that PANC-1 and MIA PaCa-2 cell growth is sustained on KRAS expression, and KRAS inhibition, but not TFEB inhibition, increased apoptosis. This is in good agreement with our published results of simultaneous gene silencing of KRAS and apoptotic genes (18). Both primary PDAC cell lines (PANC-1, MIA PaCa-2) express activating mutations of KRAS and inactivating mutations of the P53 gene (31).…”
Section: Discussionsupporting
confidence: 92%
“…The following sequences were targeted by siRNAs: KRAS 5'-GGCTATATTTACATGCTA CTA-3' [Eurofins MWG Operon, Ebersberg, Germany (18)], TFEB 5'-CACAACTTAATTGAAAGGAGA-3' (Qiagen), and KIF11 (Eg5) 5'-AACTGAAGACCTGAAGACAAT-3' as the positive control (19); and nonsense siRNA (Allstars, Qiagen) served as the negative control. All transfections were performed with a concentration of 30 nM per target gene and an incubation time of 48-72 h.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, most of the clinical trials in gene therapy have been targeting cancer treatment (64.4% of all gene therapy trials) [10, 11] with remarkable efficacies noted both in vitro and in vivo [1216]. These strategies typically include tumor cell apoptosis induction, tumor suppressor gene reintroduction, immunomodulation, oncogene inactivation and sensitivity gene introduction [12, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The KRAS is a key signaling pathway in pancreatic cancer. Typical alterations in the molecular signaling include mutations in KRAS in 95% of pancreatic cancer [41] , [51] . Consistent with our results, previous studies have also shown that ECT2 is an oncogene which is overexpressed in pancreatic tumor tissues [52] .…”
Section: Discussionmentioning
confidence: 99%